Upaya Meningkatkan Kemampuan Menulis Permulaan dengan Menggunakan Media Gambar di Kelas Rendah Sekolah Dasar - Gajah, Eni Nurhalizah; Siregar, Hotma (Universitas Pahlawan Tuanku Tambusai, 2024)
This study was prepared with the aim of improving students' beginning writing skills by using picture media in low grade students in SD Negeri 064974 Tembung, Kota Medan, Provinsi Sumatera Utara. Writing skills are one of the communication tools used to convey desires and express themselves through writing. Writing skills need to be taught to students from the early stages of primary school. Learning media is a tool used in learning and teaching activities. This type of research is Classroom Action Research (CAR), where teachers and researchers are the implementers of learning and observers. The data collection techniques used in this study were test, observation and documentation techniques. This research procedure was carried out as many as II cycles, the steps of each cycle consisted of 4 stages, namely planning, implementation, observation and reflection. The results of the research in this study showed that there was an increase in the completeness of beginning writing using picture media by 25% between Cycle I and Cycle II. In Cycle I the results obtained were 58.3% and in Cycle II an increase of 83.3% was obtained. The use of learning media is very important in the learning process, this will make learning more memorable, interesting and meaningful.